Rheology of continuous media: methodical recommendations for practical training and self-study - Kizilova, Nataliya N.; Soloviova , Olena N.; Кізілова, Наталія Миколаївна; Соловйова, Олена Миколаївна (Kharkiv : V.N. Karazin Kharkiv National University, 2023)
The methodological recommendations for the practical studies and individual tasks on the course "Fundamentals of Nanorheology" are collected. Detailed data on modern rheology, its history, technical equipment for experimental studies of the rheological properties of natural and artificial materials, as well as discrete and continuous models of viscoelastic materials, and the rheology of non-Newtonian fluids are given. The issue is prepared for the students who are interested in mathematical modeling of applied problems in mechanics of materials.
Реологія суцільних середовищ: методичні рекомендації до практичних занять та самостійної роботи
Keywords: MATHEMATICS; NATURAL SCIENCES; динаміка рідини; реологія; мікрофлюідика; нанофлюідика; нанотехнології; fluid dynamics; rheology; microfluidics; nanofluidics; nanotechnology